2018
DOI: 10.1080/10790268.2018.1451237
|View full text |Cite
|
Sign up to set email alerts
|

Pre-operative screening for asymptomatic bacteriuria and associations with post-operative outcomes in patients with spinal cord injury

Abstract: Pre-operative ASB screening is common in patients with SCI undergoing elective spine and lower limb surgery, although ASB occurs in less than 1/3rd of cases. There were no associations between pre-operative ASB and outcomes. Further studies evaluating the clinical benefit of this practice in patients with SCI should be performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…The Spanish Society of Clinical Microbiology and Infectious Diseases only recommends screening and treating AB in neurogenic or incontinent patients, as well as those with indwelling urine catheters, prior to prosthetic spinal surgery to avoid Gram-negative surgical site infections [ 41 ]. However, a recent study did not find differences in terms of surgical site infection, readmission or symptomatic UTI [ 131 ]; therefore, no consensus exists in these particular cases.…”
Section: Asymptomatic Bacteriuriamentioning
confidence: 99%
“…The Spanish Society of Clinical Microbiology and Infectious Diseases only recommends screening and treating AB in neurogenic or incontinent patients, as well as those with indwelling urine catheters, prior to prosthetic spinal surgery to avoid Gram-negative surgical site infections [ 41 ]. However, a recent study did not find differences in terms of surgical site infection, readmission or symptomatic UTI [ 131 ]; therefore, no consensus exists in these particular cases.…”
Section: Asymptomatic Bacteriuriamentioning
confidence: 99%
“…9 Several studies of both cardiac surgery and spinal cord surgeries have found no association with preoperative bacteriuria and postoperative infections. 7,[10][11][12] Despite recommendations against screening for ASB in nonpregnant adults from the US Preventative Services Task Force, or prior to nonurologic operations by the Infectious Disease Society of America, this practice has persisted. 13 Cardiothoracic surgeries have had some of the highest screening rates for urine testing preoperatively.…”
mentioning
confidence: 99%